(untitled) (Eurasian Journal of Ecology, 2024)
This study presents an analytical review of the micro/nanoplastic pollution problem in the wastewater and surface waters of the Republic of Kazakhstan. The review of published scientific works shows that analyzing micro- and nanoplastics (MNP) in the task due to their ubiquitous presence in natural habitats. This raises concerns because of their direct toxicological impact and their potential to carry hazardous pollutants and pathogens, thereby posing risks to human health and ecosystem integrity. MNPs have been detected in drinking water treatment processes, as well as in wastewater and surface waters in various regions of Kazakhstan. According to the studied data, there is a seasonal dynamic in the concentration of microplastics in water and bottom sediments, as well as in the wastewater of Astana city. It has been established that the predominant types of MNPs in surface waters are fibers, films, and granules, while polyethylene is prevalent in wastewater. Overall, the analysis of the current state of Kazakhstan’s environment in terms of micro/nanoplastic pollution indicates that such pollution exists and warrants close attention from scientists and environmental monitoring services.